Tailoring Health-promoting Programs for Patients with Chronic Kidney Disease: Randomized Controlled Trial. (February 2021) - Teng, Hsiu-Lan; Yen, Miaofen; Fetzer, Susan; Sung, Junne-Ming; Hung, Shih-Yuan
Research on dietary and lifestyle modifications to decrease cardiovascular risk and slow disease progression has been limited to patients in the later stages of chronic kidney disease (CKD). Studies on the effectiveness of stage-of-change-tailored interventions on lifestyle modifications for individuals with early stage CKD are limited. Using random assignment, 60 patients with early stage CKD who received up to six tailored intervention visits over 30 months were compared to 60 usual care patients on physical indicators, lifestyle behaviors, and quality of life. Tailored interventions were consistent with the trans-theoretical Model of Change. Waist circumference, nutrition, and stress management improved over time in the intervention group. There was no difference or change in quality of life. To promote a healthier lifestyle, findings suggest that clinicians working with patients with CKD should consider patients' readiness to change their behaviors as well as implementation strategies tailored for different processes of change.